Strong sea forcing and warmer winter during solar minima ∼2765 yr B.P. recorded in the growth bands of Crassostrea sp. from the confluence of river Ganges, Eastern India. (20th June 2018) - Banerjee, Yogaraj; Ghosh, Prosenjit; Bhushan, Ravi; Rahul, P.
Abstract: Long term variation of solar activity plays a key role in controlling climatic oscillations during glacial-interglacial cycles. The records of such climatic shifts can be retrieved from sedimentary archives in overbank deposits found in the estuary regions of major rivers in the tropics which are fed by glaciers. In this study we have shown the effect of solar variability on regional climate by altering the river discharge and incursion of warm water pool into the region adjoining Bay of Bengal during seasonal dry period. The incremental growth bands present in the modern day Meretrix sp and Late Holocene Crassostrea sp. were examined for reconstruction of temperature and water composition at the head bay region of the river Ganges. The conventional C 14 techniques on fossil oyster yielded age of 2765 ± 130 yr B·P., which coincides with a solar minima. Analysis of clumped isotope thermometry on the growth bands provided temperature estimates for the growth of shells. The temperature estimates for the modern shell, suggesting range of values showed a range between 13° and 42 °C, close to the observed temperatures recorded in the climatological data while the fossil shell had a range of values between 22° and 38 °C. The δ 18 O measured in the aragonite together with the estimated temperature were used to deduce the water composition during growth at equilibrium condition. The water δ 18 O varied between −4.8‰ and 1.2‰ for the modern sample, close to the observed values of water measured near this locality, while the range in water composition inferred for the paleo samples was from −2.37‰ to 0.82‰, suggesting a stronger influence of sea water throughout the year. The results are consistent with the argument of infiltration of water from neighbouring warm water pool into the estuary. A similar approach can be extended to evaluate the effects of climate variability due to differential action of river discharge into the sea at seasonal time scales based on available mollusc shells in the sedimentary successions from the region.